Stratégies photographiques et espaces de travail - Caroline Bach (La Nouvelle Revue du Travail)
The article focuses on how modern artists who use photography represent their working space. People conceptualise the world of work and its representation - even where this has little to do with the actual work being performed – in terms of different spatial forms, which can range from embroidery workshops or supermarkets to hospitals, museums, factories, offices and building exits. Strategies are analysed here using photographic series in which a range of approaches are applied, including documentary styles or else techniques such as differentiation, diversion and synecdoche – all used to envision the world of work in the light of the relationship between workers’ bodies and various spatial forms. The study concludes by revisiting the photographic medium’s well-known attempt to to turn itself into a metonymic force by working closely together with realism.